2021
DOI: 10.1080/16070658.2020.1769334
|View full text |Cite
|
Sign up to set email alerts
|

Overview of field-testing of the revised, draft South African Paediatric Food-Based Dietary Guidelines amongst mothers/caregivers of children aged 0–5 years in the Western Cape and Mpumalanga, South Africa

Abstract: Background: This paper provides an overview of a series of studies undertaken to assess the appropriateness and understanding of the revised, draft South African Paediatric Food-Based Dietary Guidelines (SA-PFBDGs) amongst mothers/ caregivers of children aged 0-5 years. Previous exposure to guidelines with similar messages, barriers and enablers to following the guidelines were also assessed. Design: Qualitative methods were used to collect data from 38 focus-group discussions (isiXhosa = 11, Afrikaans = 11, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…An outline of the methodology for the larger study is reported in the overview paper. 7 Study design, setting and population A descriptive, cross-sectional, qualitative study was conducted. Focus-group discussions (FGDs) were the method of data collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An outline of the methodology for the larger study is reported in the overview paper. 7 Study design, setting and population A descriptive, cross-sectional, qualitative study was conducted. Focus-group discussions (FGDs) were the method of data collection.…”
Section: Methodsmentioning
confidence: 99%
“…This study formed part of a larger study that aimed to field-test the revised, draft SA-PFBDGs amongst mothers/caregivers of children aged 0-5 years in the Western Cape and Mpumalanga provinces of South Africa. 7 The aim of this study was to determine the appropriateness and understanding of the revised, draft SA-PFBDGs and to gain insight into previous exposure to guidelines with similar messages, plus the perceived barriers to and enablers of the following thereof among mothers/caregivers of children aged 12-36 months, in the Stellenbosch municipal area, Western Cape province.…”
Section: Introductionmentioning
confidence: 99%
“…This study formed part of a larger study that aimed to field-test the revised, draft SA-PFBDG amongst mothers/caregivers of children aged 0-5 years in the Western Cape and Mpumalanga provinces of South Africa. 6 The aim of this study was to assess the appropriateness and understanding of the revised, draft SA-PFBDGs amongst among siSwati-speaking mothers/caregivers of children aged 0-36 months living in Kabokweni, Mpumalanga, South Africa. Previous exposure to guidelines with similar messages, barriers and enablers to following the guidelines were also assessed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, KNP often culls animals and provides meat to neighbouring communities, particularly schools, and to school feeding projects. This is aimed at ensuring that students have a balanced diet, that promotes the healthy growth of children and addresses the problem of stunting, which is one of the biggest challenges faced by children in South Africa and in particular the Mpumalanga province, which is one of the provinces that hosts the Kruger National Park [51][52][53]. Child stunting is particularly problematic, as it affects the children's development, health and economic development [54,55].…”
Section: Kruger National Park's Contribution To Health- Food-and Education-related Sdgsmentioning
confidence: 99%